Post a New Question

Calculus

posted by on .

22. Divide the expression before differentiating.

F(x) = (8x^3 - 1)/ (2x - 1)

Would the way to solve this problem be...
F(x) = [(8x^3) / (2x - 1)] - [(1)/(2x - 1)]
= [(4x^2)/(1)] - [(1) / (2x - 1)]
= (4x^2) - (2x-1)^-1

F'(x) = (8x + 1)

  • Calculus - ,

    No.

    The numerator is a difference of two squares, factor it, then, the denominator divides out evenly. Your answer is wrong.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question